Development of Immune Cells in the Intestinal Mucosa Can Be Affected by Intensive and Extensive Farm Environments, and Antibiotic Use - Christoforidou, Zoe; Burt, Rachel; Mulder, Imke; Gill, Bhupinder P.; Pluske, John; Kelly, Denise; Stokes, Christopher R.; Bailey, Michael; Lewis, Marie C. (Frontiers in Immunology, 2018)
Epidemiological studies have demonstrated that early exposure to farm environments during childhoods can be linked to reductions in the incidence of immune disorders, but generating an appropriate model is difficult. 108 half-sibling piglets were born on either extensive (outdoor) or intensive (indoor) farms: at 1 day old, a subset of piglets from each litter were transferred to a high-hygiene isolator facility to create differences in rearing environment either during birth/first day, or during the subsequent 56 days of life. Interactions between CD14, CD16, MHCIIDR and capillary endothelium were assessed using 4-colour quantitative fluorescence immunohistology. Effects of birth and rearing environment on the antigen-presenting micro-environment of the intestine proximal and distal jejunum (professional and stromal) were apparent at 5, 28 and 56 days after birth. However, effects on CD4+CD25+Foxp3+ Tregs in the intestinal mucosa were apparent around weaning at 28 days but had disappeared by 56 days. These Tregs were reduced in the isolator piglets compared to their farm-reared siblings, but this effect was less marked in piglets born on the extensive farm and required administration of antibiotics. Our results suggest that there may be at least two windows of opportunity in which different farm environments were influencing immune development: one during the perinatal period (up to the first day of life), and one during later infancy. Further, the differences on Tregs suggest that the effects of early life influences may be particularly critical around weaning.